2004
DOI: 10.1111/j.1524-4725.2004.30180.x
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine Carcinoma, Adenopathies, and Raised TAG-72 Serum Tumor Marker

Abstract: To our best knowledge, this is the first case in which a tumor serum marker is associated with a cutaneous apocrine carcinoma, a fact that should be confirmed with further patients. Its use in the monitoring of this infrequent skin neoplasia is also noteworthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Tumor-associated glycoprotein 72 (TAG-72) is a cell membrane mucin-like glycoprotein complex, overexpressed in many of human adenocarcinomas but not in normal tissues. 4345 In a study by Zhang et al, 46 it was demonstrated that TAG-72 is a new tissue biomarker in HCC that indicates the poor survival of patients (Fig. 5).…”
Section: Tumor Tissue Biomarkers Of Hccmentioning
confidence: 99%
“…Tumor-associated glycoprotein 72 (TAG-72) is a cell membrane mucin-like glycoprotein complex, overexpressed in many of human adenocarcinomas but not in normal tissues. 4345 In a study by Zhang et al, 46 it was demonstrated that TAG-72 is a new tissue biomarker in HCC that indicates the poor survival of patients (Fig. 5).…”
Section: Tumor Tissue Biomarkers Of Hccmentioning
confidence: 99%
“…Histologically, primary cutaneous apocrine carcinomas are invasive tumors, spreading from the reticular dermis to the subcutaneous fat tissue, forming clusters of tubular structures in different sizes and shapes [ 12 ]. Microscopically, they show considerable variability in their aspects; complex, glandular, papillary, tubular, cribriform, solid, and cord-like appearances have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…K is the slope of the calibration curve line). 31 Compared with the detection limit for time-resolved immunofluorometric assys (TR-IFMA) (0.55 U/mL), 32 immunoradiometric assay (0.8 U/mL) 33 and electrochemical immunosensors (0.1 U/mL), 34 the proposed ECL immunosensor has a lower detection limit. The lower detection limit may be the result of two factors: As shown in Figure 6B, the stability of the immunosensor was examined under the continuous scanning for 19 cycles for the detection of CA72-4 (0.1 U/mL).…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…K is the slope of the calibration curve line) . Compared with the detection limit for time-resolved immunofluorometric assys (TR-IFMA) (0.55 U/mL), immunoradiometric assay (0.8 U/mL) and electrochemical immunosensors (0.1 U/mL), the proposed ECL immunosensor has a lower detection limit. The lower detection limit may be the result of two factors: (1) the excellent conductivity and catalytic activity of PPy-NH 2 GO could greatly improve the ECL signal; (2) the large specific surface area of NH 2 GO after functionalized by PPy could fix a large amount of Ag 2 Se@CdSe.…”
Section: Optimization Of the Experimental Conditionsmentioning
confidence: 99%